Basics of Informed Logistics in Just-in-Time Production Sequencing and Supply Chain Systems - Thapa, Gyan Bahadur (Journal of the Institute of Engineering, 2014)
Informed logistics is one of the quite recent and challenging research issues in the domain of supply chain production. The real-time information is taken as one of the productivity factor in all sort of business operations. In this paper, we present a very basic and brief literature of informed logistics together with the recent developments in this area. Observing information flows among logistics functions in production processes, we explain some information technology enablers of informed logistics. We propose an ABSO model for better sharing and operation of information, and finally we indicate the applications of informed logistics in real-time scheduling. DOI: http://dx.doi.org/10.3126/jie.v9i1.10670 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 54–64